The use of kaolinite/zeolite mixtures for landfill liners. (22nd August 2005) - Guney, Yucel; Koparel, Savas
The use of kaolinite/zeolite mixtures as alternative landfill materials has been studied. The ratios of kaolinite/zeolite used were K/Z = 0.1, K/Z = 0.2 and K/Z = 0.3. To determine the geotechnical and physicochemical properties of the mixtures, their optimum moisture content, which provides the best compression out in the field, was determined by a compaction test. Also, tests for unconfined compression strength, hydraulic conductivity and consolidation were carried out. As a result, the optimum mixture was found to be K/Z = 0.2. To test the effect of contaminants, this optimum mixture was contaminated with Na, Ca, Pb, and Cu, and tests of the specific gravity, liquid and plastic limits, unconfined compression strength, consolidation, pH, and electrical conductivity were performed. It is concluded that the K/Z = 0.20 mixture has high absorption capacity and can be used in the landfill liner materials.